Public security in the pre-classical political and legal thought of ancient Greece - Y. O. Zahumenna (Law and Safety)
A thorough theoretical and legal study of the key features of general philosophical and special legal understanding and interpretation of security issues of man, society and state in the pre-classical political and legal thought of ancient Greece is given. An analysis of the views of ancient Greek authors (poets, philosophers, historians, lawyers) who are representatives of socio-philosophical and political legal thought of the period against the background of widespread collective ideas about security as a state of social relations, the condition of human (social) life and / or unique social value, objects (spheres) of this security, as well as subjects and regulatory mechanisms to ensure the appropriate state of society and the state is presented. It is proved that the ancient political and legal doctrines, which comprehend public safety, have the following main features: its nationalization (elevation of the state and its institutions in guaranteeing this security), personalization (close dependence of personal security on public, sometimes even raising personal security over public), universalization (security as a phenomenon of the space world order, general Hellenic security), rationalization (discursive understanding of public security issues), legalization (transfer of public security issues to the plane of its legal support, which becomes imperative, mandatory compliance with polis laws, a system of severe penalties for offenses in the field of public safety, law and order in society and the state), indefiniteness of the actual state and public security (which was due to the polis nature of the state system), axiologization (security as a high human and social value, as a good, as an integral element of the polis worldview and ensuring the proper organization of polis life), polymorphism (breadth of spectrum of public security and specification of its “images” in philosophy, poetry, historiography, rhetoric, etc.). It is concluded that for the vast majority of ancient Greek thinkers, security issues were related to the phenomenon of harmony between the universe, society and humanity itself. An important source of knowledge about security was considered to be the thoughts of ancient Greek philosophers about proper life and ways to achieve it. For most authors of the time, the main determinants of security were hatred, war and struggle, power and strength. Instead, they associated security with love, peace, and stability, or with a conscious refusal to use violence. For other philosophers, security was a concept of social cooperation (harmony, peace) and integration. Among the ancient Greek authors there were those who put public security in both planes at the same time, looking for its source in a kind of dialectical combination of hatred and love, war and peace, power and stability.